CONTRACEPTION AMONGST SENIOR SECONDARY SCHOOL STUDENTS IN IBADAN NORTH-EAST LOCAL GOVERNMENT AREA OF OYO STATE (1995)
Over the recent years, sexual activities among students in Secondary Schools in Nigeria, particularly those in urban areas, are thought to be high and increasing. The resultant unwanted pregnancies and illegal abortions among these young unmarried population are creating social and health problems (Nichols, et al, 1986). According to previous research findings, included in the causative factors responsible for this unfortunate situation, cure the problems of poor knowledge of Family Life (Sex Education) and Reproductive Health Education and Contraception, negative attitude towards contraceptive services, low and ineffective use of contraceptives due to low accessibility to family planning services. Therefore, the present Knowledge, Attitude and Practices (KAP) study was carried out in order to assess the level of contraceptive awareness and utilization amongst Students in Secondary Schools in- Ibadan North-East- Local Government Area of Oyo State. After the pretesting, a total number of 766 questionnaires were finally administered to students in the Senior Classes in four (4) Secondary Schools in the Local Government Area using a combination of proportional stratified and systematic random sampling techniques. The selected four (4) schools consists of one Boys' only, Girls' only and two mixed schools. Out of this number, a total of 744 duly completed questionnaires were subsequently analysed. The result showed that 484(65.1%) respondents had the correct knowledge of some modern methods of contraception, and out of this figure, 183(37.8%) mentioned condom as a popular method of contraception among them. Although, attitudinal disposition of the respondents towards contraceptive use was as high as 76.0%, however, the results showed a very low level of contraceptive utilization among them (15.7%), Based on these findings, it is suggested that Family Life and Reproductive Health Education including contraceptive counselling services should be introduced in the secondary schools in the L.G.A.